The Renaissance battle for Rome - Beer, Susanna de (Oxford University Press, 2023)
'The Renaissance Battle for Rome' examines a rhetorical battle fought simultaneously between many parties seeking prestige or legitimacy through the legacy of ancient Rome. It traces the contours of this battle across Renaissance Europe, waged by humanist Latin poets negotiating different claims on behalf of others and themselves in their work.
10.1093/oso/9780198878902.001.0001
Keywords: Latin poetry; Medieval and modern; Humanism; Renaissance; Literature; Literature: history & criticism